The Influence of Visually Dangerous Information on Imitation in Children. Issue 5 (2nd September 2020) - Zhao, Liang; Sang, Na
Abstract: Previous studies have demonstrated that when perceiving the actions of another agent, individuals will automatically imitate those observed actions. This study investigated how children's imitation of physical actions was influenced by either visually neutral or visually dangerous information. Participants were presented with a series of pictures in which an agent was reaching towards either a neutral object or a dangerous object. Results showed that the imitation effect occurred when the agent was observed reaching and grasping a neutral object. However, this effect was not present when the agent's hand was observed reaching towards or grasping, the non-handle side of a dangerous object. These results suggest children can predict potential behavioral consequences and adjust their imitative action depending on the perceived danger of the action.